ШАРАНГАДЫН АГУЙН БИЧЭЭС - О.Дэмчигмаа; Х.Бямба-Од (Acta Mongolica, 2010)
In the article the author researched inscriptions of Sharangad cave in Dundgobi aimag. There are a lot of Old Mongolian (Mongolian script) and Tibetan inscriptions about spells and prayers which related to Buddhism, especially Lamaism. The transcription, translation and some commentaries on the inscriptions have been made by the author.